Ta’ṡīr Istikhdām aṭ-Ṭarīqah as-Siyāqiyyah Fī Ta`līm Mahārah al-Kalām (Baḥṡ Tajrībī Fī aṣ-Ṣaff al-Awwal “Safīr” Bi al-Madrasah al-Mutawassiṭah al-Mutakāmilah ad-Durrah Mārilān) - Shalini Shalini (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2023)
The formulation of the problem in this research is what students' abilities are towards learning speaking skills using the method contextual and without using it in class VII "Safir" SMP IT Ad-Durrah Marelan? And is there an influence of using contextual methods on learning? Speaking skills in class VII "Safir" SMP IT Ad-Durrah Marelan? This research aims to determine students' abilities in learning skills speaking using contextual methods and without using them in class VII "Safir" SMP IT Ad-Durrah Marelan, and also to find out the influence use of contextual methods for contextual learning in class VII "Safir" SMP IT Ad-Durrah Marelan. The research method used is quantitative research with design (True Experimental) using methods Posttest Only Control Group Design. The data analysis method used is statistics. The results obtained from this research are as follows female students' ability to learn speaking skills using contextual method in class VII "Safir" SMP IT Ad-Durrah Marelan obtained a rating "Very Good", as for the results of learning speaking skills without using contextual methods in class VII "Safir" SMP IT Ad-Durrah Marelan earned a "good" rating. That there is an influence of method use contextual towards learning speaking skills in class VII "Safir" SMP IT Ad-Durrah Marelan. This shows that there is an influence of method use contextual with a high value in the experimental group.